2020
DOI: 10.1159/000511724
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Renal Replacement Therapy with oXiris® Membrane in Severe Ebstein-Barr Virus-Mediated Hemophagocytic Lymphohistiocytosis: A Case Report

Abstract: Hemophagocytic lymphohistiocytosis (HLH), a life-threatening disease with uncontrolled immune activation and inflammatory reaction, often leads to a deadly cytokine storm. In severe Ebstein-Barr virus-triggered HLH receiving standard immunosuppression, continuous renal replacement therapy (CRRT) with oXiris<sup>®</sup> blood purification membrane resulted in a timely reduction of inflammatory markers and discontinuation of vasopressors. To our knowledge, this is the first report of successful use o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…oXiris filter is superficially modified from an AN-69 membrane (polyacrylonitrile) with an additional positively charged polyimide ethylene layer used to enhance the cytokines-adsorbing capacity by ionic bonding and grafted with heparin (Broman et al, 2019), which was first approved and marketed in Europe in 2009. The addition of the highly adsorptive preheparinized oXiris filter can enhance the ability of CRRT to effectively remove endotoxin, circulating cytokines, and inflammatory chemokines, thus reducing lactate concentration and vasopressors infusion rate, and improving haemodynamic status, systemic perfusion, multi-organ function, and clinical outcomes without related adverse events (Broman et al, 2019;Schwindenhammer et al, 2019;Turani et al, 2019;Villa et al, 2020;Samman et al, 2021). Therefore, it gained emergency approval from US Food and Drug Administration (FDA) for the clinical treatment of COVID-19 in April 2020 to counter the CRS attack triggered by SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…oXiris filter is superficially modified from an AN-69 membrane (polyacrylonitrile) with an additional positively charged polyimide ethylene layer used to enhance the cytokines-adsorbing capacity by ionic bonding and grafted with heparin (Broman et al, 2019), which was first approved and marketed in Europe in 2009. The addition of the highly adsorptive preheparinized oXiris filter can enhance the ability of CRRT to effectively remove endotoxin, circulating cytokines, and inflammatory chemokines, thus reducing lactate concentration and vasopressors infusion rate, and improving haemodynamic status, systemic perfusion, multi-organ function, and clinical outcomes without related adverse events (Broman et al, 2019;Schwindenhammer et al, 2019;Turani et al, 2019;Villa et al, 2020;Samman et al, 2021). Therefore, it gained emergency approval from US Food and Drug Administration (FDA) for the clinical treatment of COVID-19 in April 2020 to counter the CRS attack triggered by SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…Study has concluded that children with HLH may require CRRT support [30,40]. Treatment with a blood puri cation CRRT membrane can signi cantly alleviate hypercytokineemia in HLH [41]. Indications for initiating CRRT include uid overload, severe metabolic acidosis, electrolyte abnormalities, and signi cant symptoms of uremia [18].…”
Section: Discussionmentioning
confidence: 99%
“…oXiris lter is super cially modi ed from an AN-69 membrane (polyacrylonitrile) with an additional positively charged polyimide ethylene layer used to enhance the cytokines-adsorbing capacity by ionic bonding and grafted with heparin (3), which was rst approved and marketed in Europe in 2009. The addition of the highly adsorptive preheparinized oXiris lter can enhance the ability of CRRT to effectively remove endotoxin, circulating cytokines, and in ammatory chemokines, thus reducing lactate concentration and vasopressors infusion rate, and improving haemodynamic status, systemic perfusion, multi-organ function, and clinical outcomes without related adverse events (3,31,32,35,37). Therefore, it gained emergency approval from US Food and Drug Administration (FDA) for the clinical treatment of COVID-19 in April 2020 to counter the CRS attack triggered by SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%